The Empirical Implications of Utility Analysis - Samuelson, Paul A. (Econometrica, 1938)
IT IS MORE THAN HALF a century since the first formulations of utility analysis by Jevons, Menger, and Walras. In that time there has been much controversy for and against this concept. Although much of the discussion has not gone beyond a quasiphilosophical defense or rejection of the utility concept, it is nevertheless possible to discern clear lines of development in the literature. First, there has been a steady tendency toward the removal of moral, utilitarian, welfare connotations from the concept. Secondly, there has been a progressive movement toward the rejection of hedonistic, introspective, psychological elements. These tendencies are evidenced by the names suggested to replace utility and satisfaction-ophelimit6, desirability, wantability, etc. The question arises as to what is left when all these elements are removed. Does not the whole utility analysis become meaningless in the operational sense of modern science? A meaningless theory according to this criterion is one which has no empirical implications by which it could conceivably be refuted under ideal empirical conditions. Thus, it is meaningless to ask whether the earth really moves around the sun rather than the sun around the earth, since no hypothesis with respect to the facts of celestial behavior is implied by either of these conventions. Is the same true of utility analysis? Has it no empirical implications for price-quantity behavior? It is clear that in its early formulations it was thought to have very definite, even revolutionary, consequences for the analysis of price and value. Moreover, even today the instinct of the textbook writer is methodologically sound in his attempt to deduce the negatively sloping demand curve from the Weber-Fechner law and diminishing marginal utility; this does not alter the fact that the whole demonstration is hopelessly fallacious and illogical. That some modern formulations of the utility concept are empty, circular, and meaningless in the above sense, is hardly open to doubt.' Consider, for example, a typical view as follows. (1) People act according to a plan; (2) a plan is how people act; (3) hence, people act as